2017
DOI: 10.1002/bjs.10572
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the influence of chemotherapy-associated liver injury on outcome after partial hepatectomy for colorectal liver metastases

Abstract: An increase in postoperative major morbidity and liver surgery-specific complications was observed after partial hepatectomy in patients with severe SD and steatohepatitis. Postoperative liver failure occurred more often in patients with severe SD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 66 publications
0
70
0
Order By: Relevance
“…In contrast, steatohepatitis is known to increase the risk of postoperative mortality when the patient receives more than 7.5 cycles of chemotherapy. Body mass index is one surrogate marker for high risk of hepatic steatohepatitis …”
Section: Chemotherapy‐associated Liver Damagementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, steatohepatitis is known to increase the risk of postoperative mortality when the patient receives more than 7.5 cycles of chemotherapy. Body mass index is one surrogate marker for high risk of hepatic steatohepatitis …”
Section: Chemotherapy‐associated Liver Damagementioning
confidence: 99%
“…Rate of increase in splenic volume and decrease in platelet count are predictive of SOS . Reportedly, 75% of patients who received adjuvant chemotherapy had increased splenic volume and 40% of patients did not recover after discontinuation of chemotherapy . Giving bevacizumab in combination with systemic chemotherapy reduces the occurrence of SOS .…”
Section: Chemotherapy‐associated Liver Damagementioning
confidence: 99%
“…Vauthey et al 49 with steatohepatitis undergoing partial hepatectomy. 52 The same authors did not find an association between irinotecan chemotherapy use and steatohepatitis, however. In the same study, severe sinusoidal dilation, associated with oxaliplatin use, was also associated with major complications (OR, 1.73; 95% CI, 1.02-2.95).…”
Section: Chemotherapy-induced Liver Injury and Postsurgical Complicmentioning
confidence: 91%
“…In contrast, Masi et al showed no deaths within 90 days in patients treated with preoperative FOLFOXIRI for a median of 22 weeks. A recent 8‐study pooled analysis showed increased odds (adjusted odds ratio [OR], 2.08; 95% confidence interval [CI], 1.18‐3.66) of liver‐specific complications (ascites, postoperative liver failure, bile leak, intra‐abdominal abscess, and bleeding) for patients with steatohepatitis undergoing partial hepatectomy . The same authors did not find an association between irinotecan chemotherapy use and steatohepatitis, however.…”
Section: Chemotherapymentioning
confidence: 99%
“…39 Although steatosis and sinusoidal dilation increases morbidity risk from bleeding and biliary fistulas, there are conflicting data as to whether sinusoidal damage or steatosis (and steatohepatitis) increase the risk of perioperative mortality after resection of CRLM. 34,35,40,41…”
Section: Chemotoxicitymentioning
confidence: 99%